Dementia prevalence and incidence in a federation of European Electronic Health Record databases: The European Medical Informatics Framework resource. Issue 2 (20th July 2017) - Perera, Gayan; Pedersen, Lars; Ansel, David; Alexander, Myriam; Arrighi, H. Michael; Avillach, Paul; Foskett, Nadia; Gini, Rosa; Gordon, Mark F.; Gungabissoon, Usha; Mayer, Miguel‐Angel; Novak, Gerald; et al.
Abstract: Introduction: The European Medical Information Framework consortium has assembled electronic health record (EHR) databases for dementia research. We calculated dementia prevalence and incidence in 25 million persons from 2004 to 2012. Methods: Six EHR databases (three primary care and three secondary care) from five countries were interrogated. Dementia was ascertained by consensus harmonization of clinical/diagnostic codes. Annual period prevalences and incidences by age and gender were calculated and meta‐analyzed. Results: The six databases contained 138, 625 dementia cases. Age‐specific prevalences were around 30% of published estimates from community samples and incidences were around 50%. Pooled prevalences had increased from 2004 to 2012 in all age groups but pooled incidences only after age 75 years. Associations with age and gender were stable over time. Discussion: The European Medical Information Framework initiative supports EHR data on unprecedented number of people with dementia. Age‐specific prevalences and incidences mirror estimates from community samples in pattern at levels that are lower but increasing over time.